Cascade Probability Method and its Relationship with Boltzmann Equations; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Kupchishin A. I. Anatoliy Ivanovich; Kupchishin A. A. Alexander; Voronova N. A. Natalia; Lisitsyn V. M. Viktor Mikhailovich (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen